Use of stable isotopes for assessing urbanization impacts on freshwater fishes - Burbank, Jacob; Drake, D. Andrew R.; Power, Michael (Frontiers in Environmental Science, 2022)
Continued urban development is inevitable with ongoing human population growth. Urbanization has profound negative impacts on aquatic environments and the organisms that occupy those environments. Urbanization results in habitat stressors including sedimentation, alterations to flow, increases in water temperature, changes in riparian habitat, and changes in the food supply of freshwater systems. In the face of continuing urbanization there is an urgent need to employ effective and practical tools to evaluate the impacts on freshwater fish populations and to better understand the implications of urban development for lotic aquatic ecosystems. Stable isotope analyses (δ13C, δ15N, δ18O δ34S and δ2H) are useful and cost-effective tools that can help highlight and evaluate urbanization impacts on fish populations. Here we review recent developments in stable isotope-based methods for studying urbanization impacts on freshwater fish populations. We identified and review published studies that have implemented stable isotopes to evaluate urban impacts, discuss promising stable isotope-based approaches that have not been commonly applied to the assessment of urban impacts, and highlight the advantages and limitations of the various approaches. In particular, we show how stable isotope analyses can help address both the ecological and physiological impacts of urban development on freshwater fishes in hopes of inspiring more frequent use of the approaches in urbanization studies. We elucidate how stable isotopes can be used to understand the impacts of urbanization on the feeding ecology, habitat and thermal occupancy, and field metabolic rates of freshwater fishes. It was found that stable isotope-based approaches are underutilized to examine the impacts of urbanization on freshwater fishes. We suggest such approaches can be applied more frequently in freshwater environments globally to help assess and actively mitigate the negative impacts of urbanization on freshwater fishes.